Mobilisasi Politik Laskar Sholawat Nusantara terhadap Tata Kelola Demokrasi Lokal Pilkada Jember 2024 - Danu Agung Fathulloh Hadi; Binaridha Kusuma Ningtyas (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
This study aims to analyse the political mobilisation mechanisms employed by Laskar Sholawat Nusantara (LSN) during the 2024 Jember Regency Election and to examine their implications for local democratic dynamics. A descriptive qualitative approach was adopted, with the research conducted in Ambulu District, Jember Regency. Data were collected through observation, in-depth interviews, and documentation involving LSN administrators, Srikandi members, religious leaders, and local voters. The data were analysed through the stages of data reduction, data display, and conclusion drawing. This study was informed by Charles Tilly’s theory of political mobilisation mechanisms, encompassing environmental, cognitive, and relational mechanisms, as well as the political participation theory developed by David F. Roth and Frank L. Wilson. The findings show that LSN’s political mobilisation operates through three main mechanisms. The environmental mechanism is characterised by public expectations for regional leadership change, which encourage participation in organisational activities. The cognitive mechanism develops through socialisation processes and the dissemination of information that shape public understanding and positive perceptions of the organisation’s activities. Meanwhile, the relational mechanism is built through social ties among religious leaders, religious study groups, and women’s networks organised within Srikandi LSN, creating trust and strengthening public support. The study also finds a transformation in women’s political participation, particularly among members of religious study groups, from relatively passive individuals into active participants in social, religious, and organisational activities. Furthermore, LSN functions as an associational interest group that expands public participation and influences local democratic processes through social networks and religious values.